Implementasi Smart Mini Book Sebagai Media Edukasi Gizi Kurang Pada Ibu Balita Di Puskesmas Antang Perumnas - Irma Irma; Puspita Dewi; Nur Alam; Nurfaidah Nurfaidah (Jurnal Dharma Abdi Lestari (JDAL), 2026)
Malnutrition among toddlers remains a public health issue that requires serious attention, as it can hinder physical growth and cognitive development and increase the risk of infectious diseases. This condition is still prevalent in the service area of the Antang Perumnas Community Health Center, influenced by various factors, one of which is mothers’ low nutritional literacy in meeting their children’s nutritional needs. Innovative, simple, and easy-to-understand educational efforts are needed to improve the knowledge of mothers of toddlers. This community service activity aims to improve nutritional literacy among mothers of toddlers through the use of the Smart Mini Book as a practical and engaging educational tool. The method employed is a pre-experimental design with a one-group pre-test and post-test approach involving 30 mothers of toddlers participating in the posyandu program. The activity stages included problem identification, baseline knowledge assessment, interactive counseling, distribution of the Smart Mini Book, and post-intervention knowledge evaluation. The content of the Smart Mini Book covered the definition of malnutrition, signs and symptoms, risk factors, prevention, and examples of balanced meal plans for toddlers. The results of the study showed that the average knowledge score of respondents increased from approximately 6.5–7.0 (fair) on the pre-test to 9.0–9.5 (good–very good) on the post-test, with more than 80% of respondents showing improvement. Thus, the use of the Smart Mini Book effectively improves maternal nutrition literacy and has the potential to serve as a sustainable educational tool in the prevention of malnutrition among infants.